A Study of The Elimination of Criminal Sanctions in The Development of Business Competition Law in Indonesia - Desi Apriani; Zulherman Idris; M. Musa; Rosyidi Hamzah; Dwi Yusuf Rafly (International Conference On Law And Social Sciences, 2024)
The Job Creation Law which was passed in 2020 brought major changes to business competition law in Indonesia. One of the changes that occurred was in the sanctions provisions for alleged monopolistic practices and unfair business competition, namely the removal of the main criminal sanctions in Article 48 paragraphs (1) and (2) and additional criminal sanctions in Article 49. This deletion gave rise to pros and cons among the public. observer of business competition law and raises its own problems and results in confusion in the provisions of law enforcement procedures. The author is interested in conducting an in-depth study so that it is answered philosophically, and has a specific aim to offer conceptually ideal recommendations so as to straighten out the controversy that has occurred. This research is normative juridical research with a statutory, historical and conceptual approach. Historically and philosophically, since the beginning of discussions on the draft law prohibiting monopolistic practices in 1998, there has been a debate regarding the conceptualization of criminal sanctions for monopolistic practices and unfair business competition. The debate about the concept of criminal sanctions occurred as a result of a dilemma between law enforcement on the one hand and reasons for investment and economic development on the other hand. The debate regarding the elimination of criminal sanctions for violations of prohibitions against monopolistic practices and unfair business competition can be reduced by putting forward more consistent and clear legislative concept. The abolition of criminal sanctions should be followed by the abolition of articles that determine whether a case can be transferred to the criminal realm. Apart from that, in order for administrative sanctions to be more effective, integration needs to be established between other related institutions, so that the decisions of business competition authorities in Indonesia have dignity.